Mutu Pelayanan Terhadap Pelanggan - Ni Nyoman Wulan Antari (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2024)
In the world economy, market gyrations have an important role in the economic cycle.This is not without reason, the basis of the statement can be created as the market was the meeting of producers, sellers and consumers ( buyers ) this meeting based on the needs of the community for the fulfillment of food as one of meeting the needs of the economy.The object and the subject of study the market kertha established in 2003 by the village and shadow of customary tanjung bungkak denpasar, presently the market located in prof kertha road area.A good idea.Engineering data collection was conducted using interviews and documentation. This study using 30 the informants.The quality of service to customers is very considered important by the kertha market.Thus, superintendent, managers and market pedangan kertha committed to provide optimal service needs of their customers.Two things that should be a commitment to, and the traders in maintaining and improving the quality of service to customers like / provides access to opportunity of the managements and traders to access a manner to give good quality of service for customers and the quality of the services provided by a proctor, the good and traders to subscribers.